Relationship between physical exercise and COVID-19 (SARS-CoV-2): systematic review - Castoldi, Robson Chacon; de Ângelo, Juliana Cristina [UNESP]; Pereira, Thiago Teixeira; Dias, Rodrigo Martins; Negrão, Fábio Juliano (Springer Nature, 2023)
Background: The SARS-CoV virus is a precursor to the SARS-CoV-2 virus (COVID-19) and has caused millions of deaths worldwide. Although exercise can be a non-pharmacological means for the prevention and treatment of various diseases, the effects on COVID-19 patients are not yet completely clear. Aims: The aim of this study was to investigate the relationship between physical exercise and symptoms caused by COVID-19. Methods: The present systematic review was sent for evaluation and received the PROSPERO registration protocol-CRD42021257475. The search for studies related to health and physical exercise was carried out in the following databases; the “National Library in Medicine MEDLINE–Ovid”, “Embase”, “Web of Science”, “SportDiscus-Ebsco”, and “Scopus”. Results: Ten articles were included in the systematic review and the findings demonstrated the protective effects of physical exercise in patients with COVID-19. These effects were observed both in symptoms and in the period of hospitalization. In addition, the results show that the benefits of physical exercise seem to collaborate both in an individual manner and as an alternative to drug therapy. Finally, it was possible to verify the effect of physical exercise on variables, such as quality of life, cardiorespiratory capacity, and immunological biomarkers, and on the symptoms of the new Coronavirus. Conclusions: It is possible to conclude that physical exercise can be a component for the treatment of COVID-19. In addition, it could help to reduce the symptoms and severity of COVID-19, and may be considered as an adjunct to drug therapy in patients contaminated with SARS-CoV-2.
Keywords: COVID-19; Physical activity; Physical exercise; Randomized Clinical Trial; SARS-CoV-2